PERANCANGAN SISTEM INFORMASI MONITORING PROGRES PENGADAAN BARANG PADA BAGIAN PENGADAAN DAN LOGISTIK INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA - ., Sutedi (Jurnal Informatika, 2012)
Informatics and Business Institute Darmajaya is a leading college in Bandar Lampung. As a leading college IBI Darmajaya should be balanced with good compliance infrastructure. the procurement functions handled by the Procurement and Logistics division that have implemented computer technology to help the processing of procurement administration. In order to increase performance procurement and logistics division, by simplify the procurement process, and also ease the staff to supervise and ensure if the procurement process goes along with the established procedure. Development of information system use analysis method and structured design.